2008
DOI: 10.1590/s0100-879x2008000600005
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms at the ADIPOR1 regulatory region with type 2 diabetes and body mass index in a Brazilian population with European or African ancestry

Abstract: Association studies between ADIPOR1 genetic variants and predisposition to type 2 diabetes (DM2) have provided contradictory results. We determined if two single nucleotide polymorphisms (SNP c.-8503G>A and SNP c.10225C>G) in regulatory regions of ADIPOR1 in 567 Brazilian individuals of European (EA; N = 443) or African (AfA; N = 124) ancestry from rural (quilombo remnants; N = 439) and urban (N = 567) areas. We detected a significant effect of ethnicity on the distribution of the allelic frequencies of both S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
(24 reference statements)
0
3
0
1
Order By: Relevance
“…Regarding this relationship, Jin et al (2014) found previously that subjects with T2DM and risk genotypes (GG+GA) in rs3737884 had lower concentrations of HDLc in a genetic association study [53]. Similarly, Yeh et al (2008) reported that a variant in the regulatory region of ADIPOR1 is associated with lower HDLc in Brazilian subjects with African ancestry [64].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Regarding this relationship, Jin et al (2014) found previously that subjects with T2DM and risk genotypes (GG+GA) in rs3737884 had lower concentrations of HDLc in a genetic association study [53]. Similarly, Yeh et al (2008) reported that a variant in the regulatory region of ADIPOR1 is associated with lower HDLc in Brazilian subjects with African ancestry [64].…”
Section: Discussionmentioning
confidence: 86%
“…In a study carried out with Finnish and Swedish adults, the SNP rs6666089 in ADIPOR1 also had no association with triacylglycerol levels [63]. Additionally, Yeh et al (2008) found no association between ADIPOR1 and serum triglycerides in a multi-ethnic Brazilian sample where two variants in regulatory regions were genotyped, which represents one of the most relevant antecedents for South American populations [64].…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, Neto et al, (2021) also detected an association between the NOS3 SNP rs1799983 and the IGFBP3 SNP rs11977526 with arterial hypertension in a sample constituted only by women from quilombos of Alagoas (NE) (Neto et al 2021). The authors also highlight the need to test for multilocus effects in the study of complex traits, as the individual polymorphisms did not show significant associations (Yeh et al 2008;Angeli et al 2011;Kimura et al 2012).…”
Section: The Genetics Of Health-related Traits In Quilombos and The I...mentioning
confidence: 99%
“…Limitar as análises a regiões candidatas do genoma reduz a necessidade de testes múltiplos a um custo de reduzir a abrangência/cobertura da análise (ROEDER et al, 2006;MARCHANI et al, 2009) et al, 2020), sendo afetadas simultaneamente por doenças resultantes da sua falta de acesso a serviços básicos (SILVA, 2007;FREITAS et al, 2011;AMORIM et al, 2013;CALDEIRA, 2016) e por doenças frequentes do mundo ocidental e moderno, como a hipertensão e a obesidade (ANGELI et al, 2011;KIMURA et al, 2012;BEZERRA et al, 2013;PAULI et al, 2019;SANTOS et al, 2019). COTRIM et al, 2004;KIMURA et al, 2016;NUNES et al, 2020), endocruzamento (LEMES et al, 2015, demografia e seleção natural (NUNES et al, 2016a(NUNES et al, , 2016b, bem como a ocorrência de doenças Mendelianas e multifatoriais, anemia falciforme (AURICCHIO et al, 2007), síndrome do X frágil (ANGELI, 2003;ANGELI et al, 2005), diabetes (YEH et al, 2008), obesidade (ANGELI, 2008ANGELI et al, 2011) e hipertensão (KIMURA et al, 2010KIMURA, 2012;PEREIRA et al, 2014). Oito dessas populações foram selecionadas para a condução desse estudo.…”
Section: Abordagem Combinadaunclassified